2020
DOI: 10.1111/jcmm.15350
|View full text |Cite
|
Sign up to set email alerts
|

Prostate‐specific membrane antigen expression in the vasculature of primary lung carcinomas associates with faster metastatic dissemination to the brain

Abstract: Glioblastomas and brain metastases (BM) of solid tumours are the most common central nervous system neoplasms associated with very unfavourable prognosis. In this study, we report the association of prostate‐specific membrane antigen (PSMA) with various clinical parameters in a large cohort of primary and secondary brain tumours. A tissue microarray containing 371 cases of ascending grades of gliomas pertaining to astrocytic origin and samples of 52 cases of primary lung carcinomas with matching BM with follow… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 39 publications
4
13
0
Order By: Relevance
“…MIF has been shown to contribute to tumor immune escape by counteracting CD8 + T cell mediated immune surveillance [46] . Vascular expression of PSMA in various tumor types has also been shown to be associated with tumor progression and poor prognosis [40] , [47] , [48] , and we also found that high proportion of tip-like ECs was correlated with poor clinical outcomes in several cancer cohorts. Thus, tip-like ECs could be used as novel therapeutic targets, with PSMA as the specific membrane molecule for targeting in non-prostate cancers.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…MIF has been shown to contribute to tumor immune escape by counteracting CD8 + T cell mediated immune surveillance [46] . Vascular expression of PSMA in various tumor types has also been shown to be associated with tumor progression and poor prognosis [40] , [47] , [48] , and we also found that high proportion of tip-like ECs was correlated with poor clinical outcomes in several cancer cohorts. Thus, tip-like ECs could be used as novel therapeutic targets, with PSMA as the specific membrane molecule for targeting in non-prostate cancers.…”
Section: Discussionsupporting
confidence: 69%
“…PSMA has been widely used as a target for the diagnosis and treatment of prostate cancer because of its high expression in prostate cancer cells [38] . Previously, PSMA has also been found to be co-localized with CD34 in tumor vasculature by using immunohistochemical staining in various tumor tissues [39] , [40] . Since CD34 was considered to be a marker of angiogenic tip cells in human vascular ECs [41] , these results confirmed the specific PSMA expression in tumor vasculature in other solid tumors.…”
Section: Discussionmentioning
confidence: 99%
“…9,39 Additionally, ex vivo images of tumors and healthy organs harvested from mice 8 h post injection showed that 4WJ-X-EGFR apt nanoparticles strongly accumulated in tumors, with low or no accumulation in the liver or other organs. 5 Prostate-specific membrane antigen (PSMA) was detected in prostate cancer cells and the neovasculature of different kinds of malignant neoplasms, including breast, 429 brain, 430,431 lung, 430 and other cancers 432 but not in normal vascular endothelium. Our previous study demonstrated ligand− receptor binding of RNA nanoparticles with PSMA aptamers (Figure 30C) and PSMA-RNA nanoparticle displaying EVs.…”
Section: Rna Nanoparticles Functionalized With Targeting Groups As Ac...mentioning
confidence: 99%
“…Prostate-specific membrane antigen (PSMA) was detected in prostate cancer cells and the neovasculature of different kinds of malignant neoplasms, including breast, brain, , lung, and other cancers but not in normal vascular endothelium. Our previous study demonstrated ligand–receptor binding of RNA nanoparticles with PSMA aptamers (Figure C) and PSMA-RNA nanoparticle displaying EVs.…”
Section: Active Delivery Of Therapeutics By Rna Nanoparticles To Dise...mentioning
confidence: 99%
“…The prostate-specific antigen (PSA) was spotted in prostate cancer cells and the neovasculature of many types of malicious neoplasms, such as breast cancer [88], lung [89], and some other tumor cells [90]. One study reported ligand-receptor relation of RNA NPs with PSA aptamers.…”
Section: Prostate Cancermentioning
confidence: 99%